Nineteenth-century English Stability and change - Kyto, Merja (Cambridge University Press, 2013)
The structure and use of the English language has been studied, from both synchronic and diachronic perspectives, since the sixteenth century.1 The result is that, today, English is probably the best researched language in the world. But the field is as unlimited as language itself, and therefore there will always be gaps in our knowledge of the historical development of English as well as of its time-bound, or synchronic, uses. In this respect, Late Modern English (1700–1950) has been given less scholarly attention than other periods in the history of English. This is particularly true of the nineteenth century and the first half of the twentieth century